(untitled) (Praxis Educativa, 2012)
This article deals with the controversial relationship between education and values in the process of citizenship construction. From a theoretical perspective, we present the design and results obtained from research carried out in the city Mar del Plata. Our inquiries were focused on student’s representations of the present world at the end of their compulsory school courses. Word associations and drawings were used as instruments to be later discussed and analyzed in order to set values and antivalues according to an Axiological Model of Integral Education (Gervilla, 1985). The role of school in the construction of student’s representations as well as in the teaching of values leading to the development of a critical citizenship are also discussed.